2021
DOI: 10.1108/cr-05-2021-0079
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the international competitiveness of polish economy system in 2004-2019

Abstract: Purpose This study aims to present the issue of the international systemic competitiveness of the Polish economy. The essence of this concept was shown, as well as the measures and methods of analysis used. The aim of the research was to identify the factors that had the greatest impact on the formation of the international systemic competitiveness of the Polish economy. Design/methodology/approach An econometric model was constructed to explain the shaping of the value of the dependent variable (gross domes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Better competitiveness is achieved through the main determinants including juridical fairness, social responsibility, competence building, and intelligence employment to develop smart patterns. Rojek [20] found that international systemic competitiveness depends on factors like government integrity, tax burdens, and investment freedom.…”
Section: Approaches and Components Of Competitivenessmentioning
confidence: 99%
“…Better competitiveness is achieved through the main determinants including juridical fairness, social responsibility, competence building, and intelligence employment to develop smart patterns. Rojek [20] found that international systemic competitiveness depends on factors like government integrity, tax burdens, and investment freedom.…”
Section: Approaches and Components Of Competitivenessmentioning
confidence: 99%